Assesment of Environment Impact of Contribution Project: Toward Green Building Certification and Compliance - Simon Parekke; Abdul Tahir; Tri Satriawansyah; Muhammad Ade Kurnia Harahap; Dewanto (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
This study aims to assess the environmental impact of a contributing project in the context of building certification and compliance with qualitative data through literature analysis and documentation and Milles & Huberman model analysis techniques. The findings from the study are expected to provide valuable insights into the environmental implications of the project, highlighting areas for improvement and opportunities to improve sustainability. The results will be crucial in informing policy decisions and guiding future initiatives in the field of green building, ultimately contributing to a more environmentally conscious and environmentally responsible development sector.